Effects of Alkali Treatment on Wettability of Coconut Fiber – Polyester Composites - Imran S Musanif; Daud O Topayung; Oktovian BA Sompie (Jurnal Ilmu dan Teknologi Kayu Tropis, 2014)
The effect of alkali treatment on the wettability of coconut fiber-polyester composites was investigated. The fibers were treated with 3% solution of NaOH for 1, 2, and 3 hours. Wettability of the fibers was measured through the measurement of polyester resin contact angle dropped on either untreated fibers or alkali treated fibers. Upon drying, the droplet on the fiber matrix was observed by analyzed software supported microscope. Contact angle decreased by alkalization, therefore the quality of bond was expected to increase. Decreasing contact angle was assumed due to the increasing of fiber surface roughness and porosity, the loss of lignin, and the loss of other impurities. The increasing quality of bond between the fiber and the matrix was believed to increase the strength properties of coconut fiber composites-polyester fiber compared to that of untreated.Keywords: coconut fiber, contact angle, droplet, wettability